Ice microfluidics : ice as size-tunable separation field and physicochemical nature of freeze concentrated solutions : doctoral thesis accepted by Tokyo Institute of Technology, Tokyo, Japan.: ice as size-tunable separation field and physicochemical nature of freeze concentrated solutions : doctoral thesis accepted by Tokyo Institute of Technology, Tokyo, Japan. ([2019]) - Inagawa, Arinori
No abstract available